Dyslipidemia in Patients with Nonalcoholic Fatty Liver Disease - Chatrath, Hemant; Vuppalanchi, Raj; Chalasani, Naga (Seminars in Liver Disease, 2012)
Patients with nonalcoholic fatty liver disease (NAFLD) often have dyslipidemia along with other features of metabolic syndrome such as obesity, diabetes mellitus, and hypertension. The dyslipidemia in NAFLD is characterized by increased serum triglycerides, increased small, dense low-density lipoprotein (LDL nontype A) particles, and low high-density lipoprotein (HDL) cholesterol. The pathogenesis of dyslipidemia in NAFLD is not well understood, but it is likely related to hepatic overproduction of the very low-density lipoprotein particles and dysregulated clearance of lipoproteins from the circulation. There is unequivocal evidence that cardiovascular disease is the most common cause of mortality in patients with NAFLD. Aggressive treatment of dyslipidemia plays a critical role in the overall management of patients with NAFLD. Statins are the first-line agents to treat high cholesterol and their dosage should be adjusted based on achieving therapeutic targets and tolerability. Although all statins appear to be effective in improving cholesterol levels in patients with NAFLD, there is more experience with atorvastatin in patients with NAFLD; furthermore, it is the only statin to date to show a reduced cardiovascular morbidity in patients with NAFLD. The risk for serious liver injury from statins is quite rare and patients with NAFLD are not at increased risk for statin hepatotoxicity. Omega-3 fatty acids are perhaps the first choice to treat hypertriglyceridemia because of their safety, tolerability, and efficacy in improving serum triglycerides, as well as their potential to improve liver disease.
Keywords: Dyslipidemia; nonalcoholic fatty liver disease; cardiovascular disease; statin hepatotoxicity